Analysis of Legal Certainty of Motorcycle Taxi Business Licensing in the National Transportation Business Classification and Regulatory System - Qurrota Ayuni Fahrunnisa; Nunik Nurhayati (Proceeding International Conference Restructuring and Transforming Law, 2026)
This study analyzes the legal certainty of motorcycle taxi business licensing in the KBLI 49424 business classification and its relationship with the national transportation regulatory system. The study uses a normative juridical method with a statutory and conceptual approach, through an analysis of the 1945 Constitution, Law Number 22 of 2009 concerning Road Traffic and Transportation, the Job Creation Law, the Government Regulation on risk-based business licensing, KBLI 49424, Ministerial Regulation of Transportation Number 23 of 2018, Ministerial Regulation of Transportation Number 12 of 2019, and the SPIONAM regulation. The results of the study indicate that motorcycle taxi businesses have been administratively recognized in the OSS-RBA system through KBLI 49424, but this recognition has not been followed by a sectoral operational licensing mechanism in the transportation sector. SPIONAM as a transportation licensing system also does not accommodate motorcycle taxis as a separate operational permit object. This situation creates a lack of synchronization between business legality in the OSS and operational legality in transportation regulations, resulting in a partial normative vacuum that weakens legal certainty, state oversight, consumer protection, and protection for business actors. Therefore, reintegration of regulations between the OSS, SPIONAM, and national transportation regulations is necessary to ensure the legality of motorcycle taxi businesses has a clearer, more coordinated legal basis and guarantees legal certainty from a state administrative law perspective.